The characterization of copper oxide with different molar concentration using sol-gel spin coating method / Nur Izzati Nasir - Nasir, Nur Izzati (2014)
In this paper, the Copper oxide (CuO) thin films were deposited on S00um quartz substrates. The objective of this research was to study the effect of different molar concentration of the CuO thin films deposited using spincoating technique. The molar concentration of CuO solutions used were 0.3M, 0.35M, 0.4M, 0.45M and 0.SM that prepared using sol-del method. These solutions were formed by dissolving copper acetate in isopropanol, diethanolamine and polyethyleneglycol. All samples were annealed at 600°C for 1 hour in a furnace. The electrical properties were measured to check their resistivity by two point probe technique. The electrical measurements showed that current increase when the concentration increase. The thicknesses were performed using the surface profiler while the surfaces morphology were characterized using Field Emission Scanning Electron Microscopy (FESEM). The films surfaces were smooth and uniformly distributed grains. The optical transmittances were measured using UV-Vis spectrometer and they decrease as their concentration increase.